Examining the link between education related outcomes and student health risk behaviours among Canadian youth: data from the 2006 National Youth Smoking Survey - Leatherdale, Scott; Pathammavong, Ratsamy; Ahmed, Rashid; Griffith, Jane; Nowatzki, Janet; Manske, Steve (Canadian Journal of Education/Revue canadienne de l’éducation, 2011)
This study examined whether student tobacco, alcohol, marijuana use and sedentary behaviour were associated with the educational outcomes of health-related absenteeism, truancy, and academic motivation in a nationally representative sample of Canadian youth. Descriptive analyses indicate a high proportion of students missed school due to health, and skipped class in the last month. Truancy increased with age, and male students are more likely to skip class, and be less academically motivated. Logistic regression models showed significant associations exist between substance use and all three educational outcomes. These findings support the need for coordinated action and funding in student health promotion. Keywords: Adolescent, Youth, Truancy, Absenteeism, Academic Motivation, Tobacco, Marijuana, Alcohol